Peristaltic Transport of Power-Law Fluid in an Elastic Tapered Tube with Variable Cross-Section Induced by Dilating Peristaltic Wave - Murad, Mohammed Ali; Abdulhadi, Ahmed M. (Iraqi Journal of Science, 2021)
The peristaltic transport of power-law fluid in an elastic tapered tube with variable cross-section induced by dilating peristaltic wave is studied. The exact solution of the expression for axial velocity, radial velocity, stream function, local shear stress, volume of flow rate and pressure gradient are obtained under the assumption of long wavelength and low Reynolds number. The effects of all parameters that appear in the problem are analyzed through graphs. The results showed that the flux is sinusoidal in nature and it is an increasing function with the increase of whereas it is a decreasing function with the increase of . An opposite behavior for shear strain is noticed compared to pressure gradient. Finally, trapping phenomenon is presented to explain the physical behavior of various parameters. It is noted that the size of the trapping bolus increases with increasing whereas it decreases as increases. MATHEMATICA software is used to plot all figures.